The State of Cellular Immunity in Children with Infectious Mononucleosis - Keldyorova Z.D; Aslonova M.R (Zien Journals, 2022)
The main feature of infectious mononucleosis in children is the defeat of the immune system, primarily the T-cell link. Undoubtedly, the low number of CD4 + lymphocytes is associated with reduced resistance to secondary infections. This requires an inadequate immunological response and leads to the chronicity of infectious processes.
Keywords: infectious mononucleosis; T-cell link